2019
DOI: 10.3758/s13415-019-00745-9
|View full text |Cite
|
Sign up to set email alerts
|

The wandering mind oscillates: EEG alpha power is enhanced during moments of mind-wandering

Abstract: What is your brain doing while your mind is wandering? This study used a within-subjects experience-sampling design to test whether episodes of mind-wandering during a demanding cognitive task are associated with increases in EEG alpha power. Alpha refers to cyclic oscillations in EEG activity at 8-12 Hz, and has been previously correlated with internally rather than externally directed cognition. Participants completed a speeded performance task with more than 800 trials while EEG was recorded. Intermittent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
92
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 38 publications
21
92
4
Order By: Relevance
“…Baldwin et al (2017), however, found an increase of alpha power during mind wandering at parietal electrodes using the probe-caught assessment method during simulated driving as well as during a vigilance task. Similar results could be observed by Compton et al (2019), who also found increased alpha power in episodes preceding reports of mind wandering during a Stroop task. Baird and colleagues (2014) also used the probe-caught method to investigate mind wandering during a vigilance task.…”
Section: Introductionsupporting
confidence: 88%
“…Baldwin et al (2017), however, found an increase of alpha power during mind wandering at parietal electrodes using the probe-caught assessment method during simulated driving as well as during a vigilance task. Similar results could be observed by Compton et al (2019), who also found increased alpha power in episodes preceding reports of mind wandering during a Stroop task. Baird and colleagues (2014) also used the probe-caught method to investigate mind wandering during a vigilance task.…”
Section: Introductionsupporting
confidence: 88%
“…In carrying out this work, it is important to recognize the general challenge of mapping brain measures to phenomenological states. For example, studies have reported increased alpha and theta power during states of mind wandering [122][123][124][125] , thereby challenging unilateral interpretations of alpha and theta synchronization as markers of internally-directed concentrated attention. In a convincing demonstration of this point, Brandmeyer and Delorme 126 found that novice meditators did not show dissociable levels of theta power between meditation and mind wandering, whereas advanced practitioners exhibited enhanced theta power during meditation relative to mind wandering.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2(b) shows that 30 reported that people with better memory had higher alpha frequencies. In addition, Compton et al 31 showed that the relative energy of alpha band increases when the person is in a wandering state which helps restore the memory function of the brain. In our study, we found that NIR LED light stimulation increases the relative energy of alpha wave, and the increase is stimulation frequency dependent, that is, the higher the stimulation frequency, the larger the increase of the relative energy of alpha wave.…”
Section: Discussionmentioning
confidence: 99%